Difference in Antibody Responses to Mycobacterium tuberculosis Antigens in Japanese Tuberculosis Patients Infected with the Beijing/Non-Beijing Genotype. (15th January 2017) - Zhao, Jingge; Shiratori, Beata; Okumura, Masao; Yanai, Hideki; Matsumoto, Makoto; Nakajima, Chie; Mizuno, Kazue; Ono, Kenji; Oda, Tetsuya; Chagan-Yasutan, Haorile; Ashino, Yugo; Matsuba, Takashi; et al.
Abstract : The Beijing genotype Mycobacterium tuberculosis (MTB), notorious for its virulence and predisposition to relapse, could be identified by spoligotyping based on genetic heterogeneity. The plasma samples from 20 cases of Beijing and 16 cases of non-Beijing MTB infected individuals and 24 healthy controls (HCs) were collected, and antibodies against 11 antigens (Rv0679c142Asn, Rv0679c142Lys, Ag85B, Ag85A, ARC, TDM-M, TDM-K, HBHA, MDP-1, LAM, and TBGL) were measured by ELISA. Compared to the HCs, the MTB infected subjects showed higher titers of anti-Ag85B IgG (positivity 58.2%) and anti-ACR IgG (positivity 48.2%). Of note, anti-ACR IgG showed higher titer in Beijing MTB infected tuberculosis (TB) patients than in HC (Kruskal–Wallis test, p < 0 . 05 ), while the levels of anti-Ag85B, anti-TBGL, anti-TDM-K, and anti-TDM-M IgG were higher in non-Beijing TB patients than in HC. Moreover, anti-Ag85B IgG showed higher response in non-Beijing TB patients than in Beijing TB patients (p < 0 . 05 ; sensitivity, 76.9% versus 44.4%). The sensitivity and specificity analysis showed that 78.8% Beijing infected individuals were negative in anti-TBGL-IgG or/and anti-Ag85B-IgG, while 75.0% of those were positive in anti-TBGL-IgA or/and anti-ACR-IgG tests. These results indicate the possibility of developing antibody-based test to identify Beijing MTB.